Nilai Heroisme dalam Narasi Digital: Analisis Semiotika Roland Barthes pada Video 'Unseen Heroes' oleh Telkom Indonesia - Setiawan, Joe Harrianto; Salsabila Meidiana Putri (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
Heroism reflects values such as empathy, sacrifice, love, and courage, which positively impact communities. Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, contributing IDR 8,573.89 trillion to the GDP and employing 97% of the workforce, can be regarded as unsung heroes due to their significant role in enhancing societal welfare. Digitalization is a crucial element in empowering MSMEs, with a reported 30% increase in income for those adopting digital platforms. This study analyzes the YouTube video